재난 현장 대응 및 상황 정보 관리 모델에 관한 연구 - Lee, ChangYeol; Kim, TaeHwan; Lee, ChangSeong (한국재난정보학회 논문집, 14(1), 2018)
Most of the disaster situation management system is focusing in the providing the situational information to support the decision of the commander. The information includes the sensing, CCTV, and weather data. Additionally, the reporting from the field agents is an axle of the data. These systems has weak in the field response capacities about the detail mission management to field agents. In this study, we focus in the development of the integrated model for SOP(Standard Operation Procedures) and situation information management. 대부분의 재난 상황 관리 시스템의 목표는 재난안전대책본부 지휘자의 정확한 상황 판단을 목표로 하고 있다. 이를 위하여 센서, CCTV, 기상 등으로부터 정보를 실시간으로 수집하고, 현장 담당자로부터 현장 상황 정보를 받아서 판단하는 형태로 구성되어 있다. 그러나 이러한 모델은 현장 담당자의 세부 임무 관리 및 임무 수행 상황에 대한 관리가 부족하여 현장 대응력 부족으로 나타나고 있다. 그러므로 본 연구는 이러한 현장 임무 수행 능력의 관리와 상황 관리를 통합적으로 진행할 수 있는 모델 개발에 초점을 두었다.